1993
DOI: 10.1111/j.1439-0396.1993.tb00815.x
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of a microbial feed phytase in diets of broiler chickens and ducklings

Abstract: Zusammenfassung Der günstige Einfluß einer mikrobiellen Phytase in Rationen für wachsende Küken und Enten Es wurde der Einfluß einer mikrobiellen Phytase im Futter auf die Phosphorfreisetzung in Rationen mit Hirse und Sojabohnenmehl mit und ohne Zusatz von CaHPO4 (Diät 4 und 5) bei wachsenden Küken und Enten untersucht. Bei Küken wurde die P‐Retention bei Zugabe von Phytase um 18% gesteigert. Verbessert wurde ebenfalls die Wachstumsrate, die Futterverwertung, die N‐Retention, der Tibia‐Asche‐ und P‐Gehalt. Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 9 publications
(2 reference statements)
5
10
0
Order By: Relevance
“…The magnitude of increment was comparable with those reported by Selle et al, 12 but lower than those reported by Farrell et al 13 in sorghum-based diets. Farrell et al 13 reported that addition of 750 FTU kg −1 phytase to sorghum-soy broiler diets improved AME n by Significant improvements in AME and AME n values of maize (2.3 and 2.6%, respectively) by the phytase addition were observed in the present study. The magnitude of improvements was comparable with those reported previously.…”
Section: Discussionsupporting
confidence: 62%
“…The magnitude of increment was comparable with those reported by Selle et al, 12 but lower than those reported by Farrell et al 13 in sorghum-based diets. Farrell et al 13 reported that addition of 750 FTU kg −1 phytase to sorghum-soy broiler diets improved AME n by Significant improvements in AME and AME n values of maize (2.3 and 2.6%, respectively) by the phytase addition were observed in the present study. The magnitude of improvements was comparable with those reported previously.…”
Section: Discussionsupporting
confidence: 62%
“…0 g/kg NPP. Increased food intake with supplemental phytase in the layer has also been observed by earlier workers (Farrell et al, 1993;Cantor et al, 1994;Kornegay et al, 1994;Rama Rao et al, 1999). Food efficiency was significantly poorer in the birds fed on diets with the lowest NPP content.…”
Section: Resultssupporting
confidence: 56%
“…Utilization of total and phytate-P was significantly improved by microbial phytase. The efficiency of microbial phytase in diets for broiler chickens and ducklings was evaluated by Farrell et al (1993), using growth rate, feed intake, phosphorus retention and tibia ash percentage as main response parameters. In both experiments, microbial phytase showed positive effects on the used experimental parameters.…”
mentioning
confidence: 99%